Temperature dependence on conductivity and thermal properties of a solid polymeric electrolyte of PVC- ZnO- LiClO4 - Rahman M.Y.A.; Ahmad A.; Mangsor M.R.; Wahab S.A. (Elsevier, 2023)
Ionic conductivity of PVC-ZnO-LiClO4 as a function of temperature was studied. The electrolyte samples were prepared by solution casting technique. The ionic conductivity was measured using impedance spectroscopy technique. The temperature dependence on the conductivity of electrolyte was modelled by Arhennius and Vogel-Tammann-Fulcher (VTF) equations, respectively. The highest conductivity of the electrolyte of 5.8 10-7 S cm-1 was obtained at 90C. It was found that the glass transition temperature of the electrolyte does not significantly vary with ZnO filler content. The percentage of weight loss of the electrolyte varies with the ZnO filler content. The electrolyte doped with 30 wt% ZnO shows the highest thermal stability with its decomposition temperature of 255'C. Crown Copyright 2008 Published by Elsevier B.V. All rights reserved.